Clonal parental effects on competitive interactions between two duckweeds - He, Lin-Xuan; Jin, Yu; Zhang, Xiao-Mei; Luo, Fang-Li; Xue, Wei; Lei, Jing-Pin; Liu, He; Yu, Fei-Hai (Frontiers in Plant Science, 2025)
IntroductionParental environments can influence offspring fitness via clonal (asexual) propagation, and such clonal parental effects may vary among plant species and depend on offspring environments as well. Consequently, clonal parental effects may alter competitive interactions between plant species, and such impacts may vary with offspring environments.MethodsWe conducted a two-phase experiment with two clonal floating duckweeds, Spirodela polyrhiza and Lemna minor. In the parental phase, S. polyrhiza and L. minor were grown separately under two distinct nutrient conditions and produced offspring ramets. In the offspring phase, the ramets produced from the parental phase were grown with or without a heterospecific neighbor under the same two nutrient conditions.Results and discussionIn the first phase, parent ramets of both species produced more biomass and offspring ramets under high nutrient availability than under low. In the second phase, nutrient availability experienced by the parents significantly affected the competitive ability of offspring in both species. Specifically, the offspring of L. minor suppressed those of S. polyrhiza more strongly when the parent of L. minor had been grown under high than low nutrient availability, although such clonal parental effects did not vary with nutrient availability experienced by the offspring. In contrast, the offspring of S. polyrhiza suppressed those of L. minor more strongly when the parent of S. polyrhiza had been grown under high rather than at low nutrient availability, but this effect occurred only under high nutrient availability for the offspring and diminished under low nutrient availability. These results suggest that clonal parental effects can influence competitiveness of plants and may vary depending on offspring environments. Our findings highlight the potential role of clonal parental effects in regulating interspecific interactions, which may further influence species composition and productivity of plant communities.